Fabrication of monolithic rGO/SiC(O) nanocomposite ceramics via precursor (polycarbosilane-vinyltriethoxysilane-graphene oxide) route. Issue 12 (15th August 2018) - Zhou, Rui; Liao, Liang; Chen, Zeng; Zhong, Lei; Xu, Xiaohui; Han, Yuchen; Zhong, Yuejin; Zheng, Yinong; Yao, Rongqian
Abstract: In this contribution, a technique based on molding polycarbosilane-vinyltriethoxysilane-graphene oxide (PCS-VTES-GO) precursors synthesized by chemical modification was introduced to fabricate monolithic rGO/SiC(O) nanocomposite ceramics. Results reveal that the monoliths pyrolyzed at different temperatures (1100–1500 °C) consist of β-SiC nanocrystals homogeneously embedded in amorphous SiO x C y /Cfree, and multilayered rGO nanosheets composited with β-SiC/SiO x C y /Cfree . Their nanocomposite structure provides an ingenious strategy for constructing complexes with good integrity, high ceramic yield and low linear shrinkage. This improvement is primarily attributed to the presence of GO (as graft polymers and sintering additives) which enlarges the cross-linking structure of precursors and inhibits the growth of β-SiC nanocrystals during the pyrolysis process. The final rGO/SiC(O) monoliths sintered at 1200 °C with higher hardness (19.81 GPa), satisfying ceramic yield (80.98%) and linear shrinkage (25.23%) promise to be candidates for making complex-shaped ceramic components in a simple and economical manner.